Multiplication of Legionella pneumophila in unsterilized tap water. - Yee, R B (1982)
Naturally occurring Legionella pneumophila, an environmental isolate which had not been grown on artificial medium, was tested for the ability to multiply in tap water. A showerhead containing L. pneumophila and non-Legionellaceae bacteria was immersed in nonsterile tap water supplying this fixture. Also L. pneumophila and non-Legionellaceae bacteria were sedimented from tap water from a surgical intensive care unit. This bacterial suspension was inoculated into tap water from our laboratory. The legionellae in both suspensions multiplied in the tap water at 32, 37, and 42 degrees C. The non-Legionellaceae bacteria multiplied at 25, 32, and 37 degrees C. A water sample which was collected from the bottom of a hot water tank was found to contain L. pneumophila and non-Legionellaceae bacteria. These legionellae also multiplied when the water sample was incubated at 37 degrees C. These results indicate that L. pneumophila may multiply in warm water environments such as hot water plumbing fixtures, hot water tanks, and cooling towers.